Can opportunistically collected Citizen Science data fill a data gap for habitat suitability models of less common species?. Issue 7 (14th May 2018) - Bradter, Ute; Mair, Louise; Jönsson, Mari; Knape, Jonas; Singer, Alexander; Snäll, Tord
Abstract: Opportunistically collected species observations contributed by volunteer reporters are increasingly available for species and regions for which systematically collected data are not available. However, it is unclear if they are suitable to produce reliable habitat suitability models (HSMs), and hence if the species–habitat relationships found and habitat suitability maps produced can be used with confidence to advice conservation management and address basic and applied research questions. We evaluated HSMs with opportunistically collected observations against HSMs with systematically collected observations. We enhanced the opportunistically collected presence‐only data by adding inferred species absences. To obtain inferred absences, we asked individual reporters about their identification skills and if they reported certain species consistently and combined this information with their observations. We evaluated several HSM methods using a forest bird species, Siberian jay ( Perisoreus infaustus ), in Sweden: logistic regression with inferred absences, two versions of MaxEnt, a model combining presence–absence with presence‐only observations and a Bayesian site‐occupancy‐detection model. All HSM methods produced nationwide habitat suitability maps of Siberian jay that agreed well with systematically collected observations (AUC: 086–0.88) and were very similar to a habitat suitability map produced from the HSM with systematically collected observations (Spearman rho: 0.94–0.98). At finer geographical scales there were differences among methods. At finer scale, the resulting habitat suitability maps from logistic regression with inferred absences agreed better with results from systematically collected observations than other methods. The species–habitat relationships found with logistic regression also agreed well with those found from systematically collected data and with prior expectations based on the species ecology. Synthesis and application . For many regions and species, systematically collected data are not available. By using inferred absences from high‐quality, opportunistically collected contributions of few very active reporters in logistic regression we obtained HSMs that produced results similar to those from a systematic survey. Adding high‐quality inferred absences to opportunistically collected data is likely possible for many less common species across various organism groups. Well‐performing HSMs are important to facilitate applications such as spatial conservation planning and prioritization, monitoring of invasive species, understanding species habitat requirements or climate change studies. Foreign Language Abstract Sammanfattning: Opportunistiskt rapporterade artobservationer av allmänheten blir alltmer tillgängliga för arter och regioner för vilka systematiskt insamlade data saknas. Det är emellertid oklart om dessa data är användbara för att producera artutbredningsmodeller, och därmed om de resulterande artutbredningskartorna tillförlitligt kan användas för att besvara grundläggande och tillämpade forskningsfrågor. Vi utvärderade artutbredningsmodeller baserade på opportunistiskt insamlade artobservationer gentemot modeller baserade på systematiskt insamlade artobservationer. Fokusart var den skogslevande fågeln lavskrika (Perisoreus infaustus) i Sverige. Vi kompletterade opportunistiskt insamlade förekomstdata med icke‐förekomstdata. För att erhålla icke‐förekomstdata frågade vi först enskilda frivilliga rapportörer om deras förmåga att känna igen fågelarter och om de rapporterade vissa arter konsekvent, och därefter kombinerade vi denna information med deras artobservationer. Vi utvärderade flera statistiska modelleringsmetoder: logistisk regression med icke‐förekomster, två versioner av MaxEnt, en modell som kombinerar en delmängd förekomster och icke‐förekomster med observationer av enbart förekomster, och en Bayesiansk modell som tar hänsyn till att rapportören eventuellt inte upptäckte lavskrikor som fanns på en plats. Alla modelleringsmetoder producerade rikstäckande artutbredningskartor för lavskrika som överensstämde väl med systematiskt insamlade observationer (AUC: 086‐0.88), och artutbredningskartor baserade på systematiskt insamlade observationer (Spearman rho: 0, 94‐0, 98). Vid finare geografisk upplösning fanns dock skillnader mellan metoder. Vid finare upplösning överensstämde de resulterande artutbredningskartorna baserade på logistisk regression med icke‐förekomster bättre med resultat från systematiskt insamlade data än andra metoder. De förklarande miljövariabler som identifierades med logistisk regression överensstämde vidare med variablerna som identifierades utifrån systematiskt insamlade data och med förväntningar baserade på artens ekologi. Syntes och tillämpning: För många arter och regioner är systematiskt insamlade artdata inte tillgängliga. Genom att komplettera opportunistiskt insamlade förekomster med högkvalitativa icke‐förekomster från ett fåtal mycket aktiva rapportörer, och sedan använda dessa i logistisk regression, erhöll vi artutbredningsmodeller och ‐kartor som liknar de från en systematisk undersökning. Vi tror att angreppssättet är användbart för många andra, mindre vanliga arter från olika organismgrupper från frivilligt insamlade data. Tillförlitliga artutbredningsmodeller är viktiga för rumslig naturvårdsplanering och prioritering, övervakning av invasiva arter och förståelsen av arters habitatkrav eller svar på klimatförändringar.